Shear strength prediction for steel fiber reinforced concrete beams without stirrups - Fasheng Zhang (2016)
This study proposes a theoretical approach based on modified compression field theory to predict the shear strength of steel fiber-reinforced concrete (SFRC) beams without stirrups. The tensile contribution of the steel fibers is considered in the tensile stress?strain constitutive equations, which take into account the distribution of the fibers. The proposed strength model is verified by comparing it with 139 shear failure tests previously conducted on SFRC and reinforced concrete beams without stirrups. The influences of concrete strength, fiber volume, shear span-to-depth ratio, and longitudinal steel ratio on predicted shear strength are also discussed. Comparisons between the predicted and experimental results show that the proposed model can estimate shear strength accurately.